Curing Kinetics of Diglycidyl Ether of Bisphenol-A using Mixture of Alkylaryltindihydride and 4,4'-Diaminodiphenylmethane - Deg, Priyanka; Kumar, Lalit; Kumar, Vinay; Deep, Gagan (Asian Journal of Chemistry, 2012)
Curing kinetics of diglycidyl ether of bisphenol-A in presence of varying molar ratios of alkylaryltindihydrides and 4,4'-diamino-diphenylmethane was investigated by the dynamic differential scanning calorimetry. The thermal stability of the isothermally cured resins was also evaluated using dynamic thermogravimetry in a nitrogen atmosphere.